STUDI KASUS PENYAKIT CACING Trichostrongylus Sp PADA SAPI DI DISTRIK SEMANGGA KABUPATEN MERAUKE - Imran Kahol; Henny V Saiya; Dance Fanggindae (Faculty of Agriculture, Musamus University, 2019)
This study revealed the type of parasitic worm disease in Ongole Peranakan (PO) cattle in Semanga District of Merauke Regency with a period of 1 month starting from February to March 2015. Study of Trichostrongylus Sp Worm Disease in Cow Ongole Breeds (PO) is very high in the District Semangga. The samples taken in this study were 200 Ongole Breeds (PO) consisting of productive males and females. The fecal examination method uses the Original and Centrifuge methods. The results of the study showed that in Semangga District nematode worm infection results (Trichostrongylus sp) The number of worm cases in bulls was 85 (42%) and in females as many as 87 tails (43.5%) Keywords: Merauke; Ongole Cross Breeds (PO); Trichostrongylus sp